Bromine–lithium exchange as a straightforward method to obtain meso-tetrakis(4-formylphenyl)porphyrin: a versatile intermediate. Issue 37 (9th September 2015) - Önal, Emel; Ahsen, Vefa; Pécaut, Jacques; Luneau, Dominique; Hirel, Catherine
Graphical abstract: Abstract: A three step, one-pot reaction has been developed for the introduction of the formyl functional group to the meso position of porphyrins. Symmetric meso -tetrakis(4-formylphenyl)porphyrin ((CHO)4 TPPH2 ), an important cornerstone in porphyrin chemistry, was obtained selectively in good yields via bromine–lithium exchange and subsequent Bouveault reaction. The meso -tetrakis(4-formylphenyl)porphyrin was fully characterized by HR-ESI, UV–vis, NMR, and single crystal X-ray diffraction.